Polynomial inequalities in quasidisks on weighted Bergman space - Abdullayev, G. A.; Abdullayev, F. G.; Tunç, E. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We continue studying on the Nikol’skii and Bernstein –Walsh type estimations for complex algebraic polynomials in the bounded and unbounded quasidisks on the weighted Bergman space.